P2-type purinergic signaling in the regulation of pancreatic β-cell functional plasticity as a promising novel therapeutic approach for the treatment of type 2 diabetes? - Mesto, Nour; Movassat, Jamileh; Tourrel-Cuzin, Cécile (Frontiers in Endocrinology, 2022)
Diabetes Mellitus is a metabolic disorder characterized by a chronic hyperglycemia due to an impaired insulin secretion and a decreased in peripheral insulin sensitivity. This disease is a major public health problem due to it sharp prevalence. Therefore, it is crucial to readapt therapeutic approaches for the treatment of this pathology. One of the strategies would be through P2-type purinergic receptors pathway via ATP binding. In addition to its well-known role as an intracellular energy intermediary in numerous biochemical and physiological processes, ATP is also an important extracellular signaling molecule. ATP mediates its effects by binding and activating two classes of P2 purinoreceptors: P2X receptors that are ligand-gated ion channel receptors, existing in seven isoforms (P2X 1 to 7) and P2Y receptors that are G-protein coupled receptors, existing in eight isoforms (P2Y 1/2/4/6/11/12/13/14). These receptors are ubiquitously distributed and involved in numerous physiological processes in several tissues. The concept of purinergic signaling, originally formulated by Geoffrey Burnstock (1929-2020), was also found to mediate various responses in the pancreas. Several studies have shown that P2 receptors are expressed in the endocrine pancreas, notably in β cells, where ATP could modulate their function but also their plasticity and thus play a physiological role in stimulating insulin secretion to face some metabolic demands. In this review, we provide a historical perspective and summarize current knowledge on P2-type purinergic signaling in the regulation of pancreatic β-cell functional plasticity, which would be a promising novel therapeutic approach for the treatment of type 2 diabetes.